2016
DOI: 10.1097/shk.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Sirt1 Activation Improves Mortality and Markedly Alters Transcriptional Profiles That Accompany Experimental Sepsis

Abstract: The sirtuin family consists of seven NAD+-dependent enzymes affecting a broad array of regulatory protein networks by primarily catalyzing the deacetylation of key lysine residues in regulatory proteins. The enzymatic activity of SIRT1 can be enhanced by small molecule activators known as SIRT1 activator compounds (STACs). We tested the therapeutic potential of the STAC SRT3025 in two preclinical models of severe infection, the murine cecal ligation and puncture (CLP) model to induce peritonitis and intratrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 0 publications
2
41
0
Order By: Relevance
“…Recently, a study showed that SIRT1 knockdown mice exhibited aggravated inflammatory signaling such as NF-kappa B in lung tissue of CLP mice [10]. Furthermore, pharmacological SIRT1 activation decreased mortality in experimental sepsis [24]. Importantly, RSV was found to effectively inhibit inflammatory responses by acting as a SIRT1 activator [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study showed that SIRT1 knockdown mice exhibited aggravated inflammatory signaling such as NF-kappa B in lung tissue of CLP mice [10]. Furthermore, pharmacological SIRT1 activation decreased mortality in experimental sepsis [24]. Importantly, RSV was found to effectively inhibit inflammatory responses by acting as a SIRT1 activator [25].…”
Section: Discussionmentioning
confidence: 99%
“…Through deacetylation of histone and nonhistone substrate, SIRT1 is involved in various metabolic and inflammatory diseases [8, 9]. Interestingly, SIRT1 activity is decreased in the liver, spleen, small bowel, and lung tissue in experimental sepsis models, and SIRT1 activation could improve the outcome of sepsis and ameliorate the associated inflammatory response [10, 11]. Besides SIRT1, another sirtuin, SIRT3, has also received considerable attention [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…have demonstrated that oral administration of SRT3025, another STAC, significantly improves a 7-day survival of septic mice induced by CLP. 19 Although in their study SRT3025 is given starting 48 h before CLP, we administered SRT1720 at 5 h after CLP. Resveratrol, a less specific Sirt1 activator, reduces AST, ALT, and histologic liver damage in septic rats induced by CLP 31 , and it decreases pulmonary edema and lung pathological alterations in the mouse model of sepsis induced by lipopolysaccharide (LPS).…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Moreover, stimulation of Sirt1 by SRT3025 reduces the levels of proinflammatory cytokines in the lungs of animals challenged with S. pneumoniae . 19 Macrophages are the major source of proinflammatory cytokines after activation. An in vitro study demonstrated that enhancing the Sirt1 expression inhibits the secretion of IL-6 and TNF-α in murine macrophages stimulated with LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation